Studies on the reproductive biology of the yellowfin porgy, acanthopagrus latus (houttuyn) - Ambok Bolong Abol Munafi
The yellowfin porgy, Acanthopagrus latus (Houttuyn) locally known as 'kichinu' or 'kibire' inhabits a wide geographical range, from the coast of the Pacific Ocean in Southern Japan to the Indian Ocean and the Gulf region. This species is rarely studied and its culture is carried out on a limited scale. However, the recent high demand and market value of this fish will make its culture important. This study was conducted to describe the reproductive biology, the development of the eggs and spawning of the captive broodstock, and the development of artificially-produced larvae and juveniles of this species.